Differentiation of Expenditures on Environmental Protection Investments in Rural Areas of Lower Silesia - Skowronek-Grądziel, Agnieszka (Zróżnicowanie nakładów inwestycyjnych na ochronę środowiska na obszarach wiejskich Dolnego Śląska, 2011)
The main aim of the study was to identify the trends concerning expenditures on environmental protection in rural areas of Lower Silesia in the years 2000–2008. The general level, rate of growth, participation in GDP as well as the structure of finances annually invested in the protection of rural environment were analysed. A ranking of voivodships with regard to the fulfilment of environmental protection and water management investments in rural areas calculated per one inhabitant was prepared. Structures of expenditures in various voivodships were compared. An attempt was made to identify the direction and scope of changes in the structure of expenditures in the analysed period. The results were used to define the position of Lower Silesia among all regions of Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 24-33
Keywords: ochrona środowiska; obszary wiejskie; nakłady na ochronę środowiska; environmental protection; rural areas; expenditures for environmental protection